2016
DOI: 10.1515/cclm-2015-0328
|View full text |Cite
|
Sign up to set email alerts
|

TBX20 loss-of-function mutation associated with familial dilated cardiomyopathy

Abstract: This study links TBX20 loss-of-function mutation to idiopathic DCM in humans for the first time, providing novel insight into the molecular mechanism underpinning DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…It has been verified that NKX2-5 can interact physically with other cardiac core transcriptional factors to form complexes, including GATA4 and TBX20 with profiles of expression and function in the heart overlapping with those of NKX2-5, and regulate synergistically the expression of multiple critical cardiac genes, including those coding for ANF, CX40, and Ca 2+ channels. 28,30,36,37) In this study, the NKX2-5 mutations identified in the patients with sporadic adult-onset DCM and congenital ASD were shown to result in significantly diminished transcriptional activation of the ANF promoter alone or in synergy with GATA4 or TBX20, suggesting that haplo-insufficiency or dominant-negative effect caused by the NKX2-5 mutations is potentially an alternative pathological mechanism of DCM as well as ASD and AVB.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…It has been verified that NKX2-5 can interact physically with other cardiac core transcriptional factors to form complexes, including GATA4 and TBX20 with profiles of expression and function in the heart overlapping with those of NKX2-5, and regulate synergistically the expression of multiple critical cardiac genes, including those coding for ANF, CX40, and Ca 2+ channels. 28,30,36,37) In this study, the NKX2-5 mutations identified in the patients with sporadic adult-onset DCM and congenital ASD were shown to result in significantly diminished transcriptional activation of the ANF promoter alone or in synergy with GATA4 or TBX20, suggesting that haplo-insufficiency or dominant-negative effect caused by the NKX2-5 mutations is potentially an alternative pathological mechanism of DCM as well as ASD and AVB.…”
Section: Discussionmentioning
confidence: 66%
“…8,[10][11][12][13][14][15][16][17][18][19][20] Although we made a genetic analysis of several cardiac core transcriptional factor genes in the two mutation carriers with DCM, including GATA4, GATA5, GATA6, TBX5, TBX20, and HAND1, as described previously, [22][23][24][25][26][27][28][29][30][31] and found no mutations, we cannot rule out the possibility that the genetic variants in other genes may also contribute to DCM in these two patients. Genome sequencing analysis may help to explain the possibility for these patients.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the genetic basis underpinning a number of these defects remains to be elucidated, the core cardiac transcription factors, which are expressed predominantly in the heart and mediate the expression of genes encoding cardiac structural proteins or regulatory proteins, are increasingly recognized as being important in the normal development of the heart (6). Mutations in certain genes encoding core cardiac transcription factors, including homeodomain-containing NK2 homeobox 5 (NKX2.5) and NKX2.6 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), GATA-binding protein (GATA) 4, GATA5 and GATA6 (17)(18)(19)(20)(21)(22)(23)(24), T-box protein (TBX) 5 and TBX20 (25)(26)(27)(28)(29), and a paired-like homeobox transcription factor, PITX2 (30-33), have emerged as major contributors to several types of congenital heart defects (2,5,6,34).…”
Section: Introductionmentioning
confidence: 99%